Unemployment and Drug Trafficking Among Suspects in Custody of the National Drug Law Enforcement Agency, Cross River State Command, Nigeria - Adeniyi, Emmanuel Kayode; Eneji, Rosemary I.; Okpa, John Thompson (European Scientific Journal, ESJ, 2019)
The objective of this study is to determine the relationship between unemployment and drug trafficking in Nigeria with particular reference to suspects in custody of the National Drug Law Enforcement Agency (NDLEA), Cross River State Command. Purposive sampling technique was adopted to select one hundred and twenty-seven (127) respondents (suspects) from the study area, to which standard questionnaires were administered. The generated data were statistically analysed using Pearson Product Moment Correlation analysis to estimate the relationship under study. The findings of the study revealed that there were significant direct relationships between unemployment and drug trafficking and between un-employability and illicit drug trade. Lack of entrepreneurial skills had a positive link with drug trafficking. As a solution, the study recommended that government at all levels should create or encourage the private sector to offer, more jobs for the teeming unemployed youths, promote small and medium scale enterprises for the unemployed through empowerment programmes and provide unemployment benefits for the jobless.